Research on digital story book for dyslexia learning: basic context of Bahasa Melayu / Syafiqah Hilwani Hamat@Mustafa - Hamat@Mustafa, Syafiqah Hilwani (2018)
Dyslexia is a difficulty in reading or interprets words, letters and number. Dyslexia has different type of disability and also different type of lesson. Dyslexia lesson are often known as decoding in order to understand each letter and words. The purpose of this research is to seek an answer in making multimedia tools for dyslexia treatment learning process. Besides, in this research is also finding the lack of learning tools in term of dyslexia basic education in bahasa melayu. This research is using quantitative method which is measuring data using question such as survey in specific people and specific area. The survey has been answer by people who specialize in education. The finding shows majority of answers agreed there is lack interactive software for basic education of dyslexia and the solution has been made by researcher by making a digital storybook that attractive and effective for dyslexic children. From this research, students from art and design majoring or education majoring can gain more knowledge about learning disability and multimedia.